In vivo Imaging of the Systemic Recruitment of Fibroblasts to the Angiogenic Rim of Ovarian Carcinoma Tumors - Granot, Dorit (2007)
Tumor-associated stroma, in general, and tumor fibroblasts and myofibroblasts, in particular, play a role in tumor progression. We previously reported that myofibroblast infiltration into implanted ovarian carcinoma spheroids marked the exit of tumors from dormancy and that these cells contributed to vascular stabilization in ovarian tumors by expression of angiopoietin-1 and angiopoietin-2. Ex vivo labeling of fibroblasts with either magnetic resonance or optical probes rendered them detectable for in vivo imaging. Thus, magnetic resonance imaging (MRI) follow-up was feasible by biotin-bovine serum albumin-gadolinium diet-hylenetriaminepentaacetic acid or iron oxide particles, whereas labeling with near-IR and fluorescent vital stains enabled in vivo visualization by near-IR imaging and two-photon microscopy. Using this approach, we show here that prelabeled fibroblasts given i.p. to CD-1 nude mice can be followed in vivo by MRI and optical imaging over several days, revealing their extensive recruitment into the stroma of remote s.c. MLS human epithelial ovarian carcinoma tumors. Two-photon microscopy revealed the alignment of these invading fibroblasts in the outer rim of the tumor, colocalizing with the angiogenic neovasculature. Such angiogenic vessels remained confined to the stroma tracks within the tumor and did not penetrate the tumor nodules. These results provide dynamic evidence for the role of tumor fibroblasts in maintenance of functional tumor vasculature and offer means for image-guided targeting of these abundant stroma cells to the tumor as a possible mechanism for cellular cancer therapy.